2005
DOI: 10.1001/archotol.131.12.1071
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of Platelet-Derived Endothelial Cell Growth Factor as a Prognostic Factor for Oral and Oropharyngeal Carcinomas

Abstract: Objective: To identify a strong prognostic biological marker for patients with oral and oropharyngeal squamous cell carcinomas. Design: We evaluated the protein expressions of 26 tumor-associated factors, including cytokines and cytokine receptors (granulocyte colony-stimulating factor [G-CSF], interleukin 10 [IL-10], G-CSF receptor [G-CSFR], and IL-12 receptor); angiogenic factors (platelet-derived endothelial cell growth factor [PD-ECGF] and vessel count); cell cycle-related proteins (p27, cyclin D1, and cyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
1
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 57 publications
0
6
1
1
Order By: Relevance
“…In oral and oropharyngeal cancer, literature data suggested that TP is a poor prognostic indicator [22, 23], while our data do not establish a correlation between TP expression and the main clinical-pathological parameters such as sex, age, cyto-histological grade, tumour size or nodal status. However, we found that patients with OSC with the higher MVD showed a better overall survival as compared to the patients with the lower MVD, probably as a consequence of 5-FU adjuvant therapy.…”
Section: Discussioncontrasting
confidence: 99%
“…In oral and oropharyngeal cancer, literature data suggested that TP is a poor prognostic indicator [22, 23], while our data do not establish a correlation between TP expression and the main clinical-pathological parameters such as sex, age, cyto-histological grade, tumour size or nodal status. However, we found that patients with OSC with the higher MVD showed a better overall survival as compared to the patients with the lower MVD, probably as a consequence of 5-FU adjuvant therapy.…”
Section: Discussioncontrasting
confidence: 99%
“…However, Tsuzuki et al (37), found no correlation between c-myc and 5-year survival of patients with oral and oropharangeal carcinomas. In our multivariate model, the increase in c-myc levels was positively statistically correlated with the risk of death.…”
Section: Discussionmentioning
confidence: 97%
“…BCL2 is an antiapoptotic gene and increased expression is associated with poor responses to systemic treatment of cancer (Andersen et al, 2005;Kausch et al, 2005). Colony stimulating factor-1 receptor (CSFR1) is involved in tumour cell invasion and migration, and high level expression is associated with poor prognosis in cancer patients (Tsuzuki et al, 2005). In various cervical cancer cell lines known to exhibit different degrees of aggressivity, the highest levels of colony stimulating factor are found in the most aggressive cell lines (Bretscher et al, 2000).…”
Section: Discussionmentioning
confidence: 99%